El estudio experimental de la función docente - García Hoz, Víctor (Revista Española de Pedagogía, 2019)
The frenzied pedocentric tendency of the last century pretended to displace the teacher to a second plane but before long people realized the pedagogical failure of that system and therefore the teaching and educational functions took again their old importance. Though this result is a consequence of the teaching function in Pedagogy the experimental branch did not delay its approach to the problem and the Experimental Pedagogy, as soon as it was founded, applied one of its tecniques to resolve so urgent a question. The author of this article, Professor of Experimental and Differential Pedagogy in the University of Madrid, divides the different qualities of the teacher as follows: objectively defined qualities and not objectively defined qualities, and these ones in physical (figure, health) and psychical qualities. García Hoz, after having made a complete study of the psychical qualities—by comparing his results with those of other investigators—clasifies them into three groups: teaching qualities, management qualities and professional vocation.
Keywords: estudio experimental; función docente; Revista Española de Pedagogía